You haven't hit your peak yet! uncommon wisdom for unleashing your full potential - Mackay, Harvey (John Wiley & Sons, Inc., 2020)
"Masterclass (title will change) collects Harvey's Mackay's decades of business leadership in all-new pieces of common sense, wisdom, advice, humor, and candid, invaluable advice for employees, bosses, and entrepreneurs. The book is broken up into hundreds of shorter easily digestible entries. Sections include The ABCs of Selling; Adversity can be your best friend; Humility, success make good business partners; What they didn't teach you in business school; How not to ride a dead horse; Ethics is about what is right, not who is right; Warning -- customers are perishable; Recognition does wonders for sense of hearing; and much, much more. Told with the straight-shooting humor that only Harvey Mackay can deliver, Masterclass is a frontlist gem that promises years of backlist sales"--
Includes index. - Online resource; title from digital title page (viewed on March 04, 2020)
Keywords: Career development; Success in business; Plan de carrière; Succès dans les affaires; BUSINESS & ECONOMICS; General; management techniques; cost-effectiveness analysis; market research